Quantification of Vapor Intrusion Pathways: An Integration of Modeling and Site Characterization. Issue 10 (29th September 2016) - Akbariyeh, Simin; Patterson, Bradley M.; Kumar, Manish; Li, Yusong
Abstract : Core Ideas: A numerical model was developed based on comprehensive field site characterization. Modeling results and field measurements were comprehensively compared. Soil anisotropic property could significantly influence vapor intrusion pathways. Vapor intrusion was highly dependent on oxygen availability. Vapor intrusion of volatile organic compounds into buildings can be a significant source of human exposure to hazardous materials. Field assessment is essential to evaluate the vapor intrusion pathways, which can be challenging due to uncontrolled site environments. Mathematical modeling is expected to play significant roles to predict indoor air contaminant concentration and to provide guidance for vapor intrusion management. Efforts on field assessment and mathematical modeling, however, are not well integrated in current vapor intrusion management practice. This work seeks to quantify vapor intrusion pathways into a slab‐on‐ground building by integrating mathematical modeling with well‐controlled field measurements under three different pressure and ventilation site conditions. Mechanisms controlling vapor intrusion pathways were identified through systematic comparisons between modeled and measured indoor air concentration, contaminant and oxygen distribution profiles beneath the building, and diffusive and advective flux under different pressure and air ventilation conditions. Enhanced horizontal oxygen movement was found to be critical to evaluate vapor intrusion pathways, which can be attributed to the soil anisotropic properties in combination with vertical penetration of oxygen from slab. The dependency of oxygen concentration in the biodegradation modeling was found to be very important to describe the biodegradation of volatile hydrocarbons.